2004
DOI: 10.1002/aoc.760
|View full text |Cite
|
Sign up to set email alerts
|

Study of the structure and stability of cobalt nanoparticles for ferrofluidic applications

Abstract: We present X-ray absorption spectroscopy (XAS) data, ultraviolet photoelectron spectra (HeI) and metastable impact electron spectra (MIES) of cobalt nanoparticles (typically 4 to 10 nm), prepared by Co 2 (CO) 8 thermolysis and pre-stabilized by smooth oxidation. We find that the particles consist of a core-shell system with a dominantly f.c.c. core and a shell in which Co-C and Co-O coordination is likely to occur. This corresponds well to the results from electron spectroscopy, that stabilization occurs via f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…16 For Fe nanoparticles we expect the same mechanism. Figure 1 shows the TEM image of the Fe nanoparticles after the 'smooth' oxidation.…”
Section: Main Group Metal Compoundsmentioning
confidence: 63%
“…16 For Fe nanoparticles we expect the same mechanism. Figure 1 shows the TEM image of the Fe nanoparticles after the 'smooth' oxidation.…”
Section: Main Group Metal Compoundsmentioning
confidence: 63%
“…[34] Secondly, pre-stabilized Co nanoparticles were deposited on SiO x substrates from suspensions in toluene. [35] STM indicated that a closed layer of the particles was obtained. Figure 6 displays the MIES (a) and UPS (b) spectra of the surface-deposited, pre-stabilized Co nanoparticles as a function of surface temperature.…”
Section: Mies and Upsmentioning
confidence: 97%
“…[35] For illustration, Figure 7 presents MIES and UPS (HeI) spectra for Pt colloids cross-linked by hydroquinone (left) and chlorohydroquinone (right) spacers. For the as-prepared films there is practically no emission for binding energies smaller than 3.5 eV.…”
Section: Characterization Of the Nanoparticle-spacer Interaction By Mmentioning
confidence: 99%
“…Magnetic nanoparticles are useful in various applications including electromagnetic devices [18], high-density storage media [19,20], ferrofluids [21], magnetic resonant imaging [22], drug delivery [23], and catalysts [24]. Magnetic metallic cobalt nanoparticles offer an interesting option as a raw material because using solid nanoparticles as a starting point instead of synthesizing them in situ simplifies the process substantially.…”
Section: Introductionmentioning
confidence: 99%